2002
DOI: 10.1200/jco.20.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Estimation of Overall Treatment Burden: Why Not Ask the Obvious?

Abstract: A direct patient estimation of overall treatment burden by a LASA indicator may serve as an end point in clinical trials, particularly when treatments with different toxicity profiles are being compared. It is complementary to physicians' ratings of specific toxicities and a major component of patient-rated symptom checklists and quality-of-life measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 37 publications
0
48
1
Order By: Relevance
“…In addition, those with health insurance, higher levels of education and ethnic backgrounds may be at risk of financial burden. The routine inclusion of treatment burden measures in clinical trials has been suggested as an important consideration to improve the evaluation of the treatment burden associated with health care interventions and management strategies [20]. Importantly, the development and application of appropriate measures in this context would also expand our understanding of this under-researched concept and the extent of the problem.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, those with health insurance, higher levels of education and ethnic backgrounds may be at risk of financial burden. The routine inclusion of treatment burden measures in clinical trials has been suggested as an important consideration to improve the evaluation of the treatment burden associated with health care interventions and management strategies [20]. Importantly, the development and application of appropriate measures in this context would also expand our understanding of this under-researched concept and the extent of the problem.…”
Section: Resultsmentioning
confidence: 99%
“…A higher score for a functional scale represents a higher level of functioning, a higher score for the global health status/QL scale a better QL, and a higher score for a symptom scale or item a higher level of symptoms or problems. In addition, a global indicator for overall treatment burden (Bernhard et al, 2002) and another for coping effort (Hurny et al, 1993) were included. These two indicators were transformed accordingly (0 -100), with higher scores indicating better QL.…”
Section: à2mentioning
confidence: 99%
“…Patient-reported measures have been used to quantify aspects of BOT in various conditions such as diabetes, chronic heart failure, cancer, chronic obstructive pulmonary disease and cystic fibrosis. Types of measured BOT include time and effort spent following medication regimes, 14 side effects of treatment, 15 and out-of-pocket expenditure. 16 A recent systematic review examined patient reported measures of BOT in chronic heart failure, diabetes and chronic kidney disease and found that the majority of studies lacked direct patient input and did not show evidence of reliability of the measures used.…”
Section: The Work Of Healthcare For Patientsmentioning
confidence: 99%